WORK LIFE BALANCE AND ITS SIGNIFICANCE IN SERVICE INDUSTRY IN INDIA - Prof. (Dr.) R. S. Rathee,; Jasmeet Singh, (Researchers World - International Refereed Social Sciences Journal, 2021)
I examined the Work Life Balance of Gen Y in service sector. At present time the advocates of further reduction in working time and time sovereignty for employees have little say. At the same time the compatibility of work & life has become the increasingly important issue.Todays youth is not aware of the ill effects of this imbalance and organizations are continuously exploiting the ambitious youth of India. This study explores the present Work life balance situation in service sector, time balance (equal time devoted to work and family) and Involvement balance (equal involvement in work & family).